Assessing the Implementation of Amanah Principle in the Management of KIP-Kuliah Funds among Muslim Students - Muhammad Rezeki Ritonga; Anriza Witi Nasution; Ahmad Kholil; Muhammad Zuhirsyan; Muhammad Zuardi (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to evaluate the implementation of the amanah principle in the use of Indonesian Smart Card for College (KIP-Kuliah) funds by Muslim students at the Medan State Polytechnic. The amanah principle is a fundamental value in Islamic teachings that emphasizes the importance of responsibility, integrity, and honesty in managing funds, including educational assistance funds. This study used a descriptive qualitative approach with data collection techniques including in-depth interviews, non-participatory observation, and documentation. The research informants were Muslim students receiving the KIP-Kuliah Islamic Finance and Banking Study Program, selected using purposive sampling. The results indicate that most students understand the importance of the amanah principle and strive to apply it in managing funds for academic needs. However, several obstacles were identified, such as the influence of a consumptive lifestyle, social pressure, and a lack of Sharia-based financial literacy, which impact optimal fund management. This evaluation emphasizes the importance of strengthening amanah values through Sharia-compliant financial training, character development, and more effective university oversight. This research is expected to provide evaluation material for program organizers and contribute to scientific research to strengthen the implementation of Islamic values in educational scholarship management.